Hydrotherapy and acupressure for restless legs syndrome: results of a qualitative part of a randomized controlled exploratory study - Siewert, J.; Kubasch, J.; Brinkhaus, B.; Teut, M.; Jansen, E. (Frontiers in Medicine, 2025)
IntroductionRestless legs syndrome (RLS) has a negative impact on quality of life and remains challenging to treat. This study explored the subjective experiences of individuals using two self-managed, non-pharmacological interventions—hydrotherapy and acupressure—for RLS, focusing on their perceived benefits, challenges, and feasibility in everyday life.MethodsWithin a three-armed randomized study we conducted qualitative interviews in both intervention groups. The semi-structured interviews were coded and analyzed using reflexive thematic analysis. Coding followed both an inductive approach, grounded in the data, and a deductive approach, guided by the study objectives. Data analysis was carried out using MAXQDA® software.ResultsA total of 12 telephone interviews (six per intervention group) were qualitatively analyzed. Participants had a mean age of 65 years (range 35–75). Six themes emerged: prior experiences, motivation, study document perception, treatment integration, perceived impact, and post-intervention use. Both groups reported symptom and sleep improvements. Increased mindfulness was more common in the acupressure group. Hydrotherapy participants noted sensory effects but also discomfort and time barriers. Both interventions were seen as practical, with acupressure being perceived as easier to apply.ConclusionParticipants of both groups reported varying degrees of RLS symptom improvement. High-quality confirmatory RCTs are needed to investigate the effectiveness of acupressure and hydrotherapy, with a focusing on practical implementation and the need for comprehensive, continuous guidance. Treatments in RLS should be location-independent to improve both participation and outcomes. Future research should further explore individualized adaptations and contextual factors influencing treatment experience and effectiveness.Trial registrationIdentifier DRKS00029960.